Effects of all-trans and 9-cis retinoic acid on differentiating human neural stem cells in vitro - Kubickova, Barbara; Martinkova, Sarka; Bohaciakova, Dasa; Nezvedová, Markéta; Liu, Runze; Brozman, Ondrej; Spáčil, Zdeněk; Hilscherova, Klara (Toxicology, 2023)
Cyanobacterial blooms are known sources of environmentally-occurring retinoid compounds, including all-trans and 9-cis retinoic acids (RAs). The developmental hazard for aquatic organisms has been described, while the implications for human health hazard assessment are not yet sufficiently characterized. Here, we employ a human neural stem cell model that can differentiate in vitro into a mixed culture of neurons and glia. Cells were exposed to non-cytotoxic 8-1000 nM all-trans or 9-cis RA for 9-18 days (DIV13 and DIV22, respectively). Impact on biomarkers was analyzed on gene expression (RT-qPCR) and protein level (western blot and proteomics) at both time points; network patterning (immunofluorescence) on DIV22. RA exposure significantly concentration-dependently increased gene expression of retinoic acid receptors and the metabolizing enzyme CYP26A1, confirming the chemical-specific response of the model. Expression of thyroid hormone signaling-related genes remained mostly unchanged. Markers of neural progenitors/stem cells (PAX6, SOX1, SOX2, NESTIN) were decreased with increasing RA concentrations, though a basal population remained. Neural markers (DCX, TUJ1, MAP2, NeuN, SYP) remained unchanged or were decreased at high concentrations (200-1000 nM). Conversely, (astro-)glial marker S100β was increased concentration-dependently on DIV22. Together, the biomarker analysis indicates an RA-dependent promotion of glial cell fates over neural differentiation, despite the increased abundance of neural protein biomarkers during differentiation. Interestingly, RA exposure induced substantial changes to the cell culture morphology: while low concentrations resulted in a network-like differentiation pattern, high concentrations (200-1000 nM RA) almost completely prevented such network patterning. After functional confirmation for implications in network function, such morphological features could present a proxy for network formation assessment, an apical key event in (neuro-)developmental Adverse Outcome Pathways. The described application of a human in vitro model for (developmental) neurotoxicity to emerging environmentally-relevant retinoids contributes to the evidence-base for the use of differentiating human in vitro models for human health hazard and risk assessment.
Keywords: Tretinoin; buněčná diferenciace; Retinoids; alitretinoin; nervové kmenové buňky; Alitretinoin; lidé; receptory kyseliny retinové; Receptors, Retinoic Acid; Neural Stem Cells; Humans; Cell Differentiation; tretinoin; retinoidy